2002
DOI: 10.1152/jn.2002.88.4.2075
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the Effects of Cycloheximide on Mossy Fiber Sprouting and Epileptogenesis in the Pilocarpine Model of Temporal Lobe Epilepsy

Abstract: A feature of animal models of temporal lobe epilepsy and the human disorder is hippocampal sclerosis and Timm stain in the inner molecular layer (IML) of the dentate gyrus, which represents synaptic reorganization and may be important in epileptogenesis. We reassessed the hypothesis that pre-treatment with cycloheximide (CHX) prevents Timm staining in the IML following pilocarpine (PILO)-induced status epilepticus (a multifocal model of temporal lobe epilepsy), but allows epileptogenesis (i.e., chronic spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 47 publications
3
44
0
2
Order By: Relevance
“…Other groups have challenged these observations. Williams et al (2002) reported that treatment with cycloheximide did not block either hilar cell loss or MF sprouting and that recurrent epileptic seizures can occur even in cycloheximide-treated rats.…”
Section: Is Mossy Fiber Sprouting a Cause Or Results Of Tle?mentioning
confidence: 99%
“…Other groups have challenged these observations. Williams et al (2002) reported that treatment with cycloheximide did not block either hilar cell loss or MF sprouting and that recurrent epileptic seizures can occur even in cycloheximide-treated rats.…”
Section: Is Mossy Fiber Sprouting a Cause Or Results Of Tle?mentioning
confidence: 99%
“…However, no correlation was found between MFS and seizures frequency and intensity. Whether MFS does or does not seem to be necessary for SRS development is still under debate (Longo and Mello, 1998;Pitkanen et al, 2005;Tauck and Nadler, 1985;Williams et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, inhibition of mossy fiber sprouting may not be sufficient for prevention of poststatus epileptogenesis; while administration of the protein synthesis inhibitor cycloheximide blocked mossy fiber sprouting after either pilocarpine or kainite, spontaneous seizures developed with the same frequency (Longo and Mello 1997). While other studies have found cycloheximide to be less efficacious for preventing mossy fiber sprouting, they have also found that poststatus spontaneous seizures could develop without mossy fiber sprouting as detected by Timm staining (Williams and others 2002). …”
Section: Poststatus Epilepticus Modelsmentioning
confidence: 99%